Short-Video Addiction and Academic Dishonesty Among University Students: The Mediating Role of Fear of Failure and Self-Regulation Factors - Ahmad Khairul Shiddiq; Mustari S. Lamada; Dwi Rezky Anandari Sulaiman (Sakura Digital Nusantara, 2026)
Purpose: Academic dishonesty is a critical concern in higher education, increasingly exacerbated by digital distractions like short-video platforms. Recent evidence indicates 77% of students report fear of failure as a primary reason for cheating. Yet, the interplay between digital addiction, psychological self-regulation, and integrity remains underexplored in contemporary environments. Purpose: This study investigates relationships between short-video addiction, emotion regulation difficulties, time management, fear of failure, and academic dishonesty among university students. Methods: A quantitative cross-sectional approach involved 336 undergraduates from Universitas Negeri Makassar. Data were collected via online survey using validated scales and analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) with SmartPLS 4 software. Findings: Short-video addiction significantly predicted academic dishonesty, with emotion regulation difficulties emerging as a significant indirect predictor. Fear of failure mediated these relationships, transforming psychological distress into unethical behavior. Unexpectedly, time management skills indirectly positively predicted dishonesty, contrary to hypotheses, suggesting an overcommitment trap among high-achievers facing performance pressure rather than protection against misconduct. Research Implications: Universities should prioritize reducing psychological stigma around failure and promoting digital wellbeing over punitive measures. Interventions targeting emotion coping may reduce misconduct. Educators should emphasize mastery learning over competitive grading. Additionally, policy reviews regarding student overcommitment are necessary. Conclusion: Short-video addiction directly drives unethical behavior, while emotion dysregulation operates indirectly through failure anxiety. Uniquely, time management skills indirectly correlate with increased dishonesty, indicating organization may serve grade preservation rather than learning integrity. Interventions must address psychological distress and digital wellbeing to foster honesty. Originality: This study uniquely integrates short-video addiction with self-regulation factors through fear of failure, uncovering a paradoxical time management role in Indonesian higher education contexts.